(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
Virtual reality grabs people’s attention. This technology is used in many sectors such as medicine, industry, education, video games or tourism. Perhaps the biggest area of interest is leisure and entertainment. Regardless of the sector, the adoption of virtual or augmented technology had several limitations: it was expensive, had poor ergonomics, or it took too much work to create content. Recent technological innovations, including the rapid introduction of smartphones into society, have made it easier for anyone to access virtual and augmented technology and use it in many ways. In addition, several large companies such as Apple, Facebook, Samsung and Magic Leap, among others, have increased their investments to make these technologies more affordable in the sphere of education over the next few years. Educational institutions will benefit from the increased availability of virtual technologies; this will allow teaching in virtual environments that cannot be visualized in physical classrooms, such as access to virtual labs, visualization of machines, industrial plants, or even medical scenarios. The vast possibilities of available virtual technologies will allow teachers and students to go beyond formal education.